(untitled) (Bangladesh Journal of Medical Education, 2014)
This study explores the perceptions of students of the features of effective clinical teaching and learning in dental education. This was a qualitative study conducted in one government and one private dental college selected purposively. Study population was final year dental students of selected Dental colleges. A total of 29 students participated in this study. An open ended questionnaire was developed for the focus group discussion for the students. From the students focus group discussion the following seven themes were identified, (1) Organization of the teaching and learning session, (2) stimulating and encouraging teaching and learning session, (3) achieving goal, (4) learning objectives, (5) active participation, (6) scope of frequent brief practice, and (7) feedback. These themes were further subdivided into 26 sub-themes. The features of clinical training experiences that dental students perceived were effective. Our students perceived that authentic clinical experiences are important to their clinical learning, allowing them to see the patient as a whole, be the first medical contact for the patient, and take more responsibility of their own learning and apply patient-centered care. Students also identified the importance of the scope of clinical cases they saw in terms of numbers, variety, offering varied clinical signs and unusual and interesting cases. Our students also felt that their teachers positive attitudes, ability to establish a good supervisory relationship were important to learning. It has also been shown that students value good feedback in clinical teaching and learning. Our students also felt that the learning environment contributes to their learning. DOI: http://dx.doi.org/10.3329/bjme.v2i1.18129 Bangladesh Journal of Medical Education Vol.2(1) 2011: 1-5